Andine kropsopfattelser. Relationer mellem aymaras kropsbegreb og sundhedssystem - Hansen, Mette Bech (Tidsskriftet Antropologi, 2019)
The Aymara of Bolivia have different ways of healing their illnesses and use different sources of knowledge in the health system. According to their traditional practice they tend to start curing on a home basis using their own knowledge and experience. Otherwise they may consult the local “curanderos” who exercise different abilities. Resorting to the official medical system is rare. Apart from a specific knowledge of the effects of plants, minerals, and animal ingredients it is shown that their concept of the body influences the choice of healers and healing methods. The body concept is essentially a concept of balancing body liquids and the relation between body and nature. The latter gives evidence to talking about cultural embodiment and using the body as a metaphor of the Andean society.